Supply Chain Risk Management of Liquefied Natural Gas (LNG) in Australia - Ankhi, Abida Sultana (Curtin University, 2017)
This research examines the supply chain risk management of Australia’s Liquefied Natural Gas (LNG) supply chain. The study develops a risk management methodology based on quality function deployment and 0-1 multiobjective optimization model. The research reveals 33 LNG supply chain risks and 30 risk management strategies (RMSs) for Australian LNG supply chain. Optimal sets of RMSs are found using the methodology which would be beneficial for the LNG risk managers in a limited resources scenario.